Death Education and the Management of Fear of Death Via Photo-Voice: An Experience Among Undergraduate Students. Issue 5 (18th August 2019) - Testoni, Ines; Piscitello, Marco; Ronconi, Lucia; Zsák, Éva; Iacona, Erika; Zamperini, Adriano
Abstract: The article presents the results of a research intervention aimed at exploring the differences among some factors (death anxiety, ontological representation of death as annihilation, alexithymia, spirituality, resilience, happiness) in two different groups of university students: one that attended a course of Death Education (DeEd; 83 students: DeEd-gr) and another one that did not participate in it (149: NoDeEd-gr). The DeEd course utilized the photo-voice as an elective strategy aimed at facilitating the performative experience. It was hypothesized that this method could help DeEd-gr in sharing emotions and spiritual experiences while managing the increase of death anxiety, inevitably caused by the death-related issues introduced during the lessons. The results confirmed that, despite the higher death anxiety, the DeEd-gr had a greater level of happiness and lower alexithymia compared with NoDeEd-gr, suggesting that the use of photo-voice can be useful in the course because it facilitates the management of communication and relationships. A further analysis was realized to explain the relationships between the different dimensions considered. Results evidenced that spirituality was inversely correlated with the representation of death as annihilation and with alexithymia, which was positively related to personal happiness. However, in DeEd-gr, spirituality impacted less on happiness, while the representation of death as annihilation impacted significantly more on resilience among participants of NoDeEd-gr. The discussion analyzes some characteristics that differentiated women and men, compared with men, and considers how DeEd courses should recognize the role of the ontological representations of death with their relationships with spirituality.